The effect of land use changes on runoff generation in the High Tatras region - HLAVČOVÁ, Kamila; HORVÁT, O.; SZOLGAY, Ján; DANKO, M.; KOHNOVÁ, Silvia (Contributions to Geophysics and Geodesy, 2008)
The impact of land-use changes on the runoff regime in the High Tatras region was estimated with an emphasis on the parameterization of the land cover properties in a runoff simulation. A spatially distributed physically-based hydrological model FRIER was applied to simulate runoff generation under unchanged and changed land use conditions. The Poprad river basin was divided into a number of grid cells for which the water and energy balance were maintained and hydrological processes were simulated continuously both in time and space. Parameters of the hydrological model were calibrated on data from the period of 1981-2000. The land use changes connected to agricultural and forest management were expressed by several scenarios. The effect of the changes in surface runoff, interflow, base flow, and total runoff in the basin's outlets and changes in runoff distribution on the basin after the wind calamity in 2004 were compared and discussed.